USE OF MULTIMEDIA-BASED LEARNING APPROACH IN TEACHING PRONUNCIATION: AN ANALYSIS - Novita, M.IT, Loly (Menara Ilmu, 2017)
Multimedia-based learning approach used in language learning teaching will giveimprovement in pronunciation learning. Elements of multimedia involved in (text, sound,video, animation) can make the teacher maximize his teachig process so that the learning goalscan be achieved effectively. In teaching Pronunciation a teacher is to make the studentspronounce the words correctly as well as consider the stress and intonation in order thecommunication runs well. By applying the multimedia-based learning in Pronunciationteaching, the teaching or learning will be more interesting and productive so that the students’understanding about language will improve from time to time. Although the weaknesses of thisapproach will occur during the time of teaching learning process take place, it can be takeninto account as one of the effective approaches in language teaching.Keywords—The importances of pronunciation, sound types,multimedia-based learning in thepronunciation teaching, effectiveness of the multimedia-based learning in pronunciation, morespecific strengths of multimedia-based learning approach in teaching pronunciation, someproblems in applying multimedia-based learning in pronunciation